2012
DOI: 10.1002/adsc.201200420
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐Catalyzed Hydration of Alkynylphosphonates to β‐Ketophosphonates

Abstract: A highly efficient palladium(II)-catalyzed hydration of a wide range of alkynylphosphonates to the corresponding b-ketophosphonates has been developed to give high yields at 80 8C in 1, 4-dioxane, with no acidic or alkaline cocatalysts required. The described catalytic system should provide an efficient alternative to highly toxic mercury-catalyzed methodologies and be useful in synthetic programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(36 citation statements)
references
References 68 publications
0
32
0
4
Order By: Relevance
“…In 2013, Gao and Xu reported the Pd(II)‐catalyzed hydration of alkynylphosphonates to β ‐ketophosphonates. When dialkynylphosphine oxides were subjected to the standard conditions, double hydration products 2 were obtained (Scheme a) . Interestingly, in our recent investigation, we found that when gold(I) complexes were added instead of Pd(II), the chemoselectivity of the reaction was switched from double hydration to a hydration/intramolecular cyclization cascade.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013, Gao and Xu reported the Pd(II)‐catalyzed hydration of alkynylphosphonates to β ‐ketophosphonates. When dialkynylphosphine oxides were subjected to the standard conditions, double hydration products 2 were obtained (Scheme a) . Interestingly, in our recent investigation, we found that when gold(I) complexes were added instead of Pd(II), the chemoselectivity of the reaction was switched from double hydration to a hydration/intramolecular cyclization cascade.…”
Section: Methodsmentioning
confidence: 99%
“…PdCl 2 was also examined in both DCE and dioxane. As a result, the double hydration product 2 a was obtained as main product in both DCE and dioxane (entries 20–21), which is in accordance with the literature reports . p ‐TSOH ( p ‐toluenesulfonic acid) was reported as an efficient catalyst for promoting the hydration/cyclization cascade of 1,4‐diyn‐3‐ones .…”
Section: Methodsmentioning
confidence: 99%
“…1 [2-(4'-甲基苯乙基)-2-氧代]膦酸二异丙酯(2b) [41] : 淡黄色油状物. 1 [2-(4'-甲氧基苯乙基)-2-氧代]膦酸二异丙酯(2c) [40] : 淡黄色油状物. 1 [2-(4'-溴苯乙基)-2-氧代]膦酸二异丙酯(2e) [42] : 淡 黄色油状物.…”
Section: 目标产物的合成unclassified
“…[8] Recently, Xu and Gao disclosed an efficient method for the preparation of β-oxophosphine oxides through palladium-catalyzed hydration of alkynylphosphonates (Scheme 1c). [9] Although these methods are undoubtedly useful, the development of new methods allowing greener and operationally simple synthesis from easily accessible starting materials is still highly desirable.…”
Section: Introductionmentioning
confidence: 99%